(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2024)
Business owners, particularly those in the micro, small, and medium-sized enterprise (MSME) sector, face many challenges in managing their operations and making informed decisions. Accounting practices, the backbone of financial management, are crucial in addressing these challenges and propelling business growth. This study delved into the extent to which MSMEs adhered to standard accounting practices, shedding light on their compliance levels and the underlying motivations. The study employed a quantitative approach, specifically the descriptive survey method, to gather and analyze data on the compliance levels of MSMEs across five key components: People, Documents, Equipment, Records, and Processes. This holistic approach provided a comprehensive assessment of the accounting practices in place within these businesses. The study focused on the public market of San Fernando, La Union, a vibrant hub of MSMEs. A purposive sampling technique was employed to select 44 MSMEs with at least five years of experience, ensuring a representative sample of the market’s business landscape. The findings revealed that MSMEs exhibited moderate compliance with standard accounting practices. However, a concerning aspect emerged: MSMEs primarily adhered to these practices solely for compliance purposes rather than utilizing them as tools for informed decision-making. This suggests that the true potential of accounting practices remains untapped within these businesses. Also, a statistically significant relationship exists between the number of employees and the level of accounting compliance. This suggests that as MSMEs expand and employ more individuals, they are more likely to adopt and adhere to standard accounting practices. Recognizing the need for improved accounting practices, the researchers developed an accounting handbook specifically tailored for MSMEs. This practical guide emphasizes proper accounting and tax compliance, ensuring accurate filing and recording of transactions. By providing MSMEs with clear and concise guidelines, this handbook has the potential to enhance their financial management practices. The study highlights the moderate compliance levels of MSMEs with standard accounting practices, indicating a need for further education and support in this area. While compliance is essential, MSMEs must recognize the transformative power of accounting in enabling informed decision-making and fostering business growth. By embracing accounting as a strategic tool, MSMEs can navigate the complexities of business operations with greater confidence and pave the way for sustainable success.